Ethnopharmacognosy study, antioxidant activity, and chemical content in chicken bile - Slamet Tuty; Irda Fidrianny; Sukrasno (Institut Teknologi Bandung, 2022)
The aim of this research was to study the ethnopharmacognosy, antioxidant activity, and chemical content of chicken bile. In addition, a bioactivity-guided isolation was also performed to identify compounds in chicken bile having antioxidant activity. Extraction was carried out by reflux method. Each extract was tested for its antioxidant activity using DPPH and CUPRAC methods. Fractionation was performed on selected extract, namely ethyl acetate extract, using vacuum liquid chromatography and subfraction using preparative TLC method and classical column chromatography (CCC). Compound 1 was characterized and identified by NMR, compound 2 was characterized and identified by LC-MS/MS and NMR, subfraction 7 was characterized by GC-MS. The result of the antioxidant activity of ethanol extract of chicken bile using the DPPH method (IC 50: 46.64 g/mL), ethyl acetate extract (IC 50: 69.99 g/mL), n-hexane extract (IC 50: 71.65 g/mL, fraction 15-17 (IC 50: 88.77 g/mL) showed strong antioxidant, whereas by CUPRAC method all extracts (EC 50: 69.90, EC 50: 80.28, EC 50: 70.40) and fraction (EC 50: 64.53) are strong antioxidants. The result of identification of compound 1 by NMR was identified as cholesterol, identification of compound 2 by LC-MS/MS was (E)-hexadecyl-ferulate and subfraction 7 which was identified by GC-MS produced dominant compounds, namely oleic acid, n-hexadecanoic acid, octadecanoic acid and palmitoleic acid. In conclusion, extract, fraction 15-17 and subfraction of chicken bile have antioxidant activity where the active antioxidant compound is a phenol group compound, namely (E)-hexadecyl-ferulate. The other chemical constituents found in chicken bile are, oleic acid, n-hexadecanoic acid, octadecanoic acid, and palmitoleic acid.